Socioeconomic and educational determinants of nutritional status among children under five - Esmiralda, Esmiralda; Nursyahraeni, Nursyahraeni; Hasnidar, Hasnidar; Sulfianti, Sulfianti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Nutritional status in children under five remains a critical public health concern, especially in low- and middle-income countries. Socioeconomic and educational factors play a pivotal role in determining nutritional outcomes. This study aimed to investigate the relationship between socioeconomic status, parental education, and the nutritional status of children aged five and under. Methods: A cross-sectional design was employed, involving 150 children aged 6–59 months. Data were collected through structured questionnaires assessing parental education, household income, and other demographic factors. Nutritional status was assessed using anthropometric indicators, including weight-for-age, height-for-age, and weight-for-height, based on the WHO growth standards. Data analysis used chi-square and logistic regression to identify significant associations. Results: The study found that 32% of children were undernourished, with 18% stunted and 14% underweight. Children from low-income families and those whose mothers had only a primary education were more likely to experience malnutrition (p < 0.05). Maternal education emerged as the strongest predictor of a child’s nutritional status after controlling for income and occupation. Conclusion: Socioeconomic and educational factors are significant determinants of nutritional status in children under the age of five. Improving parental education, especially among mothers, and addressing poverty are essential to combating malnutrition. Strengthen community-based nutrition education programs, promote women’s education, and develop poverty reduction strategies to ensure equitable access to nutritious food and healthcare services.